2014
DOI: 10.1177/1059601114553512
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Tenure and Employee Performance

Abstract: Previous research has investigated the relationship between organizational tenure and performance by focusing primarily on organizational tenure of the individual employee. We propose that this approach is limited because organizational tenure should be conceptualized as relating to multiple entities including teams and their leaders. As predicted, analysis of two objective performance indicators of 1,753 employees working with 250 leaders of natural work teams in a financial services company revealed that, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 79 publications
2
54
1
Order By: Relevance
“…Nevertheless, realizing the promise of team diversity has proven itself to be an intricate challenge, as a large body of evidence has shown that both objective and perceived diversity can also result in negative or non-significant effects on team outcomes (Bell, 2007;Hoever, van Knippenberg, van Ginkel & Barkema, 2012;Joshi & Roh, 2009;Stahl, Maznevski, Voigt & Jonsen, 2010;Steffens, Shemla, Wegge, & Diestel, 2014;van Knippenberg & Schippers, 2007;Wegge, Roth, Neubach, Schmidt & Kanfer, 2008). Hence, leveraging the potential that this diversity entails has become a key concern for managers.…”
Section: Team Diversity and Elaboration Of Task-relevant Informationmentioning
confidence: 99%
“…Nevertheless, realizing the promise of team diversity has proven itself to be an intricate challenge, as a large body of evidence has shown that both objective and perceived diversity can also result in negative or non-significant effects on team outcomes (Bell, 2007;Hoever, van Knippenberg, van Ginkel & Barkema, 2012;Joshi & Roh, 2009;Stahl, Maznevski, Voigt & Jonsen, 2010;Steffens, Shemla, Wegge, & Diestel, 2014;van Knippenberg & Schippers, 2007;Wegge, Roth, Neubach, Schmidt & Kanfer, 2008). Hence, leveraging the potential that this diversity entails has become a key concern for managers.…”
Section: Team Diversity and Elaboration Of Task-relevant Informationmentioning
confidence: 99%
“…Length of job tenure has been found to be positively associated with productivity, possibly because it leads to increased employee commitment and the creation of firm specific skills and knowledge (e.g. Auer et al, 2005;Dearden et al, 2006;Ng and Feldman 2010;Steffens et al, 2014). On the other hand, if tenure is extended as a consequence of fixed-term contracts being renewed, the affected workers may become demoralised and less committed, which might have negative implications for productivity.…”
Section: Productivity Flexibility and Labour Market Reformmentioning
confidence: 99%
“…Human capital resource has been operationalized, for example, as tenure, experience, and education, with tenure and experience (which is a kind of tenure) being the most commonly used measures (Nyberg, Moliterno, Hale, & Lepak, 2014). Tenure, or more specifically, organizational tenure, indicates the time that an individual has spent with an organization (Steffens, Shemla, Wegge, & Diestel, 2014) or the length of employment within an organization (Ng & Feldman, 2010). When aggregated to the team level, organizational tenure describes the average work experience and job-related knowledge of the members of that team (Ng & Feldman).…”
Section: The Moderating Role Of Organizational Tenure In the Teammentioning
confidence: 99%
“…Specifically, longer-tenured employees have greater organization-specific knowledge, including information about the functioning of the organization and its strategic direction, policy, rules, culture, and stakeholders (e.g., clients; Ng & Feldman, 2010). Longer-tenured employees also have a better understanding of the organization's expectations of employees' roles and responsibilities (Chatman, 1989;Steffens et al, 2014) and tend to perform more effectively (Ng & Feldman). Consistent with these individual-level arguments and based upon CET theory (Nyberg & Ployhart, 2013), our expectation is that team organizational tenure attenuates the negative effects of team turnover (in terms of task conflict).…”
Section: The Moderating Role Of Organizational Tenure In the Teammentioning
confidence: 99%
See 1 more Smart Citation